Infographics in corporate sustainability reports: Performance information or impression management strategy? - Alzikri Maula Deva; Ani Wilujeng Suryani (Sustinere: Journal of Environment and Sustainability, 2026)
The use of graphics in sustainability reports can serve as a means of impression management, raising concerns regarding the credibility of the information presented. This study aims to investigate impression management strategies in sustainability reports by comparing the use of graphics across different reporting periods. A visual content analysis was conducted to identify the characteristics of the graphics based on specific categories. The findings indicate that companies tend to use graphics to highlight positive performance by amplifying certain achievements and minimizing the exposure of less favorable results in order to build a favorable reputation. Moreover, differences were found in the use of graphics between reporting periods, reflecting a shift in the approach to presenting sustainability data. These findings underscore the importance of presenting graphics objectively and transparently to maintain reporting credibility and to raise stakeholders’ awareness of potential visual manipulation.